Real-world relationships as binary relations - Pinkrová , Zuzana; Honzík , Lukáš; Aichinger , Daniel (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
This contribution deals with real-world relationships as examples of binary relations. It studies the properties of binary relations such as reflexivity, symmetry, transitivity, … These binary relations are defined with the usage of real-life surroundings (like family, games, public transport, etc.). First, this work will explain the basic theoretical concepts, which are needed to examination of properties of binary relations. And in the second part it will applies the theoretical concepts to specific examples from real-world such as “be a sibling” or “rock paper scissors”.